Mechanisms of polymer-templated nanoparticle synthesis: contrasting ZnS and Au - Podhorska,L; Delcassian,D; Goode,AE; Agyei,M; McComb,DW; Ryan,MP; Dunlop,IE (Langmuir, 2016)
We combine solution small-angle X-ray scattering (SAXS) and high-resolution analytical transmission electron microscopy (ATEM) to gain a full mechanistic understanding of substructure formation in nanoparticles templated by block copolymer reverse micelles, specifically poly(styrene)-block-poly(2-vinyl pyridine). We report a novel substructure for micelle-templated ZnS nanoparticles, in which small crystallites (~4 nm) exist within a larger (~20 nm) amorphous organic-inorganic hybrid matrix. The formation of this complex structure is explained via SAXS measurements that characterize in situ for the first time the intermediate state of the metal-loaded micelle core: Zn2+ ions are distributed throughout the micelle core, which solidifies as a unit on sulfidation. The nanoparticle size is thus determined by the radius of the metal-loaded core, rather than the quantity of available metal ions. This mechanism leads to particle size counter-intuitively decreasing with increasing metal content, based on the modified interactions of the metal-complexed monomers in direct contrast to gold nanoparticles templated by the same polymer.